2005
DOI: 10.1080/09540120500120419
|View full text |Cite
|
Sign up to set email alerts
|

Violence against substance-abusing South African sex workers: intersection with culture and HIV risk

Abstract: The Republic of South Africa has become an epicentre of heterosexual HIV transmission among Black women, and the interface between violence against women, substance abuse, and HIV risk is becoming evident. This paper describes the characteristics of Black South African women who engage in sex work in Pretoria and examines their intersecting experiences of high-risk sexual behaviour, substance abuse, and victimization. Ninety-three women were recruited into the study. Field staff collected biological measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 14 publications
11
130
3
Order By: Relevance
“…Wechsberg et al 28 noted that South African female sex workers, especially the younger women and those doing drugs, depend on sex work as their main source of income, including support for other family members. These women reported abuse by men -clients, boyfriends, partners, and family -and great fear of future victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Wechsberg et al 28 noted that South African female sex workers, especially the younger women and those doing drugs, depend on sex work as their main source of income, including support for other family members. These women reported abuse by men -clients, boyfriends, partners, and family -and great fear of future victimization.…”
Section: Discussionmentioning
confidence: 99%
“…In most sex work settings, competition for clients is intense, resulting in workers going along with each client's demands for fear of losing the client or earning less. 33,36,47,123,125,[129][130][131] Time and availability of condoms are the third and fourth themes. Sex workers have described their encounters, especially with casual partners, as brief, with minimal conversation or negotiation.…”
Section: Commercial Sexual Relationshipsmentioning
confidence: 99%
“…Lawrence, Wilson, Eldridge, Brasfield & O'Bannon, 2001). However, only a small number of randomized trials have shown that brief, empowerment theory-based, individual interventions can be adapted to reduce HIV risk behaviours among substance-using South African women (Wechsberg, Luseno, & Lam, 2005;Wechsberg et al, 2006). Preliminary data from an ongoing study in Pretoria, South Africa, also suggest that such interventions can address contextual issues, such as experiences with victimization and communication about condom use with partners .…”
Section: Introductionmentioning
confidence: 99%
“…CT-WHC was adapted from an evidence-based intervention known as the Women's CoOp (Wechsberg, Lam, Zule & Bobashev, 2004;Lyles et al, 2007). This intervention was developed for substance-abusing African-American women in the United States and adapted for Black African women in Pretoria Wechsberg et al, 2005). CT-WHC further adapted the intervention for both Black African and Coloured South African women in the Western Cape of South Africa using both individual and group formats.…”
Section: Introductionmentioning
confidence: 99%